Multi-Tenant Architectures in Modern Cloud Computing: A Technical Deep Dive - Rishi Kumar Sharma (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution and implementation of multi-tenant architectures in modern cloud computing environments, focusing on their role in Software-as-a-Service solutions. The article examines how these architectures enable efficient resource sharing while maintaining strict data isolation among tenants. This article demonstrates how integrating AI-driven observability frameworks and advanced security mechanisms, such as IAM and KMS, can improve scalability by 70% and reduce operational costs by 60%, offering practical solutions to modern multi-tenant architecture challenges. The article delves into core technical components, including data layer implementation and compute layer architecture, while analyzing advanced security measures and AI-driven observability frameworks. Through extensive case studies and research analysis, the article demonstrates how multi-tenant architectures have revolutionized cloud service delivery by optimizing resource utilization, enhancing operational efficiency, and ensuring robust security measures across various industry sectors.